Roleplayer World: Identitas Roleplayer, Relasi, dan Komunikasi - Hildawati Hildawati (Emik, 2022)
Indonesia is one of the countries with a fairly large number of K-pop fans, which is also supported by a significant number of social media users. These two aspects create a phenomenon that is popular among fans who are active on social media, named roleplayers. Roleplayer is a term that refers to K-pop fans who create a fictional figure through a new identity on social media and live their lives and roles through such identity while keeping their true identity a secret. This article focuses on the virtual communication method that roleplayer has improved from K-pop fans. This study was conducted between March and July 2022, involving 18 informants who were interviewed through Zoom Meeting and Goggle Meet. Virtual participant observation was also carried through Twitter as one of the most dynamic and crowd social media with the researcher being a roleplayer and observing the uploads of roleplayer accounts and being directly involved in their communication. The roleplay performed by K-pop fans on social media Twitter is a fictional figure with a new identity called a roleplayer. Roleplayers live a double life with different identities, one as a roleplayer who "lives" in a virtual space and the other is a real self who lives in an actual space. Their lives in the actual world with real identities are called real life, while the roleplayer world is a "space" where they "live" with a fictional identity. Roleplayer identity and real identity must be strictly separated so that life in the roleplayer world and real life do not intersect with each other. In an effort to develop identity, roleplayers create story lines, namely a series of essays of events/stories made by roleplayers, so that it is as if the essay is a "journey of life" for them. In addition, roleplayers also establish relationships with other roleplayers, both personally and in groups. Communication is needed in carrying out these relationships. However, because the existence of roleplayers only revolves around Twitter and closes themselves to direct interaction, their method of communication is limited to text by utilizing Twitter features. However, roleplayers strive to be able to communicate as much as possible by improvising their communication methods through the use of special terms and abbreviations, imagining through text, and visualizing the text through images or videos. Basically, all identities attached to roleplayers are just fantasy or fictitious being transferred to a virtual space. But all the affection felt by the roleplayers is real, especially when a roleplayer is in a relationship with other roleplayer. Therefore, the fantasy that exists in the relationship becomes a "common property" fantasy that is connected to each other.